Economic Policy Uncertainty and Firm Performance in the Czech Republic - Nestoroska, Ivanka (Journal of Accounting, Business and Finance Research, 2020)
The business environment undergoes a number of changes due to the decisions made by the government and politicians of a particular country and this impacts the performance of the firms that operate in that business environment. In other words, the uncertainty in decisions of the government and politicians and the policies made by them impact the financial decisions of the firms. In this regard, the current study has been conducted to discover and examine the affect casted by EPU on the performance of the company within Czech Republic. Financial data has been collected from the public non-financial companies of Czech Republic. The data has been collected for the time of 29 years. The data gathered against the most reliable databases such as World Bank Development Indicators and Global Economy about the required variables. The GMM estimation technique was applied on the collected data and the results were obtained. The results obtained indicate that unreliability has significant as well as bad effect on the performance of the company and in opposite way; the interest rate has significant along with positive impact on firm’s performance. But the inflation rate’s impact is notable and rare only in case of net profit margin proxy of the performance of the company. Practical implication of the knowledge is for non-financial firms of Czech Republic and it might assist them in designing policies and regulations regarding the precautionary measures which can be taken in case of EPU so that the financial performance of the firms is not disturbed.